Pelaksanaan dan masalah dakwah ikatan Da’i Indonesia di Aceh / Azhari Jailani Daud - Azhari Jailani , Daud (2017)
Aceh is the first entry of Islam into the archipelago of south of east Asia named Nusantara. Admission of Islam was approved as early as the first century AH brought by the Islamic missionaries of Arab and Indian traders. of Aceh, Islam then spread to the rest of the archipelago by peaceful means. The long journey of preaching Islam in Veranda of Mecca’s land gives a very in-depth study of the interaction of Islam as peaceful and blessed religion with local people. Evident from the beginning until now Islam remains the religion and beliefs of the people of Aceh which will guide the life of society and state. Aceh is the only state in Indonesia that implement Islamic law so it will be a role model for other states in the implementation of religious life and society in harmony. This study aimed to investigate the role of the organization named Association of Indonesian Da'i (IKADI) states dakwah efforts in Aceh, identifying the dakwah efforts that have been made, and identify the problems faced dakwah. This study was conducted using qualitative descriptive method to collect data about IKADI Aceh’s activities. The data collected through documentation, observation and interviews. The study found that the dakwah efforts of IKADI Aceh include a teacher for people with educating people do Islamic activities restore the people to the nature of Islam with lectures and sermons on various occasions, be a partner of government (umara ') in a variety of programs, empowers people to Islam, especially in the fields of economics and education, provide a bulwark against apostasy and knitter brotherhood to all agencies and Muslims. Of the efforts that have been undertaken, there are weaknesses in IKADI Aceh that have been identified, including: lack of documentation and program activities so much information that is not up to the public, lack of adequate technology, particularly in the mastery of social media and the lack of human resources, especially in terms of quantity.